Observation of the melt dynamics during laser remote fusion cutting - Burger, Silvana; Dilger, Pablo; Schwarzkopf, Karen; Staudt, Tobias; Schmidt, Michael (Procedia CIRP, 2022)
Laser remote fusion cutting (RFC) offers a method for laser fusion cutting of metal sheets without need for a cutting gas. It is closely related to laser keyhole welding, which can transition into RFC for suitable parameters, such that the pressures in the process zone lead to a melt ejection on the bottom of the metal sheet. The mechanisms leading up to the melt expulsion are not fully understood yet and need further investigation. In this work, the cutting front is observed through a borosilicate glass sheet using a high-speed imaging system. In the setup, the glass sheet and a sample metal sheet are clamped together and the process zone is set directly at the interface between metal and glass. This setup allows for the observation of the melt dynamics adjacent to the glass sheet. In the experiments, the keyhole formation and the cutting front are investigated using a 6 kW disk laser and different feed velocities for cutting.<br